1993
DOI: 10.1080/00288233.1993.10427485
|View full text |Cite
|
Sign up to set email alerts
|

Introduction, production, and persistence of five grass species in dry hill country

Abstract: A trial was conducted on a seasonally dry slope near Taupo as part of a national series investigating the persistence and productivity in dry hill country of five grass species established from overs owing under contrasting nitrogen (N) and summer grazing regimes. The average annual total herbage accumulation (HA) (1983-87) was greatest from phalaris (Phalaris aquatica L. 'Grasslands Maru') swards (12100 kg DM/ha, 65% Maru); followed by a species mixture (11700 kg DMlha); tall fescue (Festuca arundinacea Schre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Moloney (1991) found that mixtures that included tall fescue and cocksfoot produced more dry matter than ryegrass alone in central North Island regions. Pure sowings of cocksfoot or tall fescue also outyielded ryegrass in the central North Island (Moloney et al 1993). In moist North Island conditions, Hainsworth et al (1991) and Judd et al (1990) found that ryegrass produced more than cocksfoot or tall fescue.…”
Section: Discussionmentioning
confidence: 94%
“…Moloney (1991) found that mixtures that included tall fescue and cocksfoot produced more dry matter than ryegrass alone in central North Island regions. Pure sowings of cocksfoot or tall fescue also outyielded ryegrass in the central North Island (Moloney et al 1993). In moist North Island conditions, Hainsworth et al (1991) and Judd et al (1990) found that ryegrass produced more than cocksfoot or tall fescue.…”
Section: Discussionmentioning
confidence: 94%
“…The application of 300 kg N ha )1 increased the total chlorophyll content in the cocksfoot leaves from 0AE55 g m )2 in irrigated plants with N deficiency to 0AE96 g m )2 in non-N-deficiency plants for the 21-day regrowth period (P. Peri, unpublished data). Ultimately, any reduction in Pmax will limit canopy expansion and therefore light interception, leading to differences in pasture growth (Donohue et al, 1981;Moloney et al, 1993;Peri et al, 2001). It follows that decreased chlorophyll formation during nitrogen deficiency decreased the photosynthetic potential of the leaf by decreasing protein content and activity (Evans, 1996).…”
Section: Nitrogen Functionmentioning
confidence: 99%
“…For example, RuBisCO enzyme activity, obtained from gas exchange measurements, has been reported to vary positively in proportion to leaf nitrogen content (Sims and Pearcy, 1989). Ultimately, any reduction in Pmax will limit canopy expansion and therefore light interception, leading to differences in pasture growth (Donohue et al, 1981;Moloney et al, 1993;Peri et al, 2001).…”
Section: Nitrogen Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first year (Table 3) Kara dominated the mixture, by the second it was equal to Roa but by the third year Roa dominated (54% v. 20% of TDM). This sudden change in composition can be explained by: a high sowing rate of cocksfoot relative to tall fescue (600 V. 800 seeds/m2 respectively -ideally this should have been 200 v. 800) (Tables 4 and 5); long rotation lengths in the first year particularly over autumn and winter; and an increase in the amount of nitrogen applied (from 50 to 90 kg N/ha/year), which would have favoured tall fescue (Moloney et al 1993).…”
Section: Two On-farm Evaluations Of Grasslands Wana and Karamentioning
confidence: 99%